Analisis Viskositas Lube Oil Di Turbin Unit 2 PLTP Lahendong - Rizqie Emeninta Putri; Jeferson Polii; Alfrie Musa Rampengan (Jurnal FisTa : Fisika dan Terapannya, 2024)
Viscosity, also known as fluid viscosity, is a fluid characteristic that provides shear stress resistance by the fluid. Viscosity describes a fluid's resistance to a flow so that it can be used to measure fluid friction. The viscosity of a lubricant is affected by changes in temperature and pressure. The pressure increases if the value of the viscosity increases, the higher the pressure, the more significant the fluid's viscosity. This study aims to find out the viscosity value of lube oil in turbine unit 2 of the Lahendong PLTP. Based on the results of the calculation, the result was obtained from the viscosity value of lube oil in turbine unit 2 of 373.61 kg/ms with a pressure of 30591.486 kg/m2, and the viscosity value increased by 386.06 kg/ms due to an increase in pressure of 31611.2 kg/m2.